Chocolate couvertures development from combination of CCN51 and Super Tree cocoa varieties, in the Pastaza Province - Enríquez-Estrella, Miguel (2022)
Dark chocolate coatings contain a high percentage of cocoa, which is pleasing to the consumer’s taste. The aim of the research was to develop a bitter-type chocolate coating from the combination of CCN51 and super tree cocoa. In this study, an experimental method, with 18 treatments was applied. In the sensory analysis a hedonic scale test with 30 untrained judges and 15 trained ones was carried out, applying a completely random unifactorial design. The judges determined that T1 treatment with a content of 70% cocoa liquor, had a mean value of 3.8, while the value for the untrained judges was not significance. A bromatological analysis of the best treatment was made based on the NTE INEN 621:2010, resulting in moisture content of 37.86%, fat 9.26%, protein 2.04% and ash 99.38%, defatted cocoa dry extract 98.41%, dry extract of total cocoa and microbiological results less than 100 ufc.ml-1 in total mesophiles, yeasts and total coliforms, parameters that are within the permissible limit.